Progress on cholesterol metabolism and non-alcoholic steatohepatitis - LI Xiao-xiao, SHU Xiang-bing, ZHANG Li (Jichu yixue yu linchuang, 2022)
Non-alcoholic steatohepatitis (NASH) is a progressive form of non-alcoholic fatty liver disease (NAFLD). Cholesterol is an essential substance for biological process. Intestinal absorption of dietary cholesterol, as well as circulating lipoprotein exchange, intracellular cholesterol synthesis and metabolism influence hepatic lipid metabolism. It is indicated that the dysfunction of organelles and the secretion of inflammatory cytokines contributed to the activation of cholesterol-loaded macrophage. Besides, cholesterol and bile acid metabolism can also trigger to the development and progression of NASH.